A data-driven methodology for characterization of a terminal manoeuvring area in multi-airport systems. (February 2020) - Amaro Carmona, Manuel Angel; Saez Nieto, Francisco; Verdonk Gallego, Christian Eduardo
Highlights: Trajectory analysis could be used to determine the deviation of aircraft trajectories. Predicting deviation patterns in the airspace helps to improve air traffic control. Determining where/when are conflicts produced help to release the airspace. London's terminal airspace contains high-adherence and low-adherence routes. Abstract: This paper proposes a methodology to characterize and evaluate the performance of the aircraft operation in complex systemized terminal manoeuvring area based on the study of its standard routes structure and their actual traffic. The methodology is composed of two main components. The first component identifies recurrent patterns by calculating the 4D adherence to the standard routes and flight plan. This process is based on the comparison of the Spatio-Temporal (S-T) differences between the actual and planned trajectories. The second component identifies and characterizes concurrence events based on the analysis of the standard routes and the along-track deviation derived from the first component to analyze the causes that produce recurrent patterns in the terminal airspace. The developed framework is applied to a study case of a representative Multi-Airport System (MAS). The quantitative effectiveness of the framework is derived by simulations using historical traffic data samples of the London Terminal Manoeuvring Area (LTMA).